Separation of molecules, macromolecules and particles : (Woodhead Publishing Limeted, 1996)
This book reviews methods and techniques for separating food components and products of the biotechnology industry. The introduction focuses on food composition and some of the conventional separation techniques. Subsequent chapters deal with each specific type or area of application individually and include information on the basic principles, industrial equipment available, commercial applications and an overview of research and development.